1989
DOI: 10.1007/bf00378663
|View full text |Cite
|
Sign up to set email alerts
|

Effects of available P and N:P ratios on non-symbiotic dinitrogen fixation in tallgrass prairie soils

Abstract: Prescribed burning is a major control over element cycles in Tallgrass prairie (Eastern Kansas, USA). In this paper we report potential effects of fire on nonsymbiotic nitrogen fixation. Fire resulted in additions of available P in ash, which may stimulate nitrogen fixation by terrestrial cyanobacteria. Cyanobacterial nitrogenase activity and biomass responded positively to additions of ash or P in laboratory assays using soil. Further assays in soil showed that cyanobacteria responded to changes in available … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
80
3

Year Published

2012
2012
2020
2020

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 130 publications
(85 citation statements)
references
References 14 publications
2
80
3
Order By: Relevance
“…The rate and amount of soil N-fixation activity is associated with the development of the organic C and N composition in soils, and is also known to be regulated by a feedback inhibition mechanism that is activated in the presence of higher N:P ratios or lower concentrations of P (Eisele et al 1989, Smith 1992, Israel 1993, Almeida et al 2000, Schulze 2004, Pons et al 2007, Reed et al 2007. This is consistent with the results of our work in which there were somewhat greater concentrations of total N and much lower concentrations of P in the PM-L soils, resulting in higher N:P ratios (i.e., P limited), greater soil C biomass, greater rates of both C and N biomass production, and a more fungaldominant microbial community in the PM-L soils.…”
Section: Discussionmentioning
confidence: 99%
“…The rate and amount of soil N-fixation activity is associated with the development of the organic C and N composition in soils, and is also known to be regulated by a feedback inhibition mechanism that is activated in the presence of higher N:P ratios or lower concentrations of P (Eisele et al 1989, Smith 1992, Israel 1993, Almeida et al 2000, Schulze 2004, Pons et al 2007, Reed et al 2007. This is consistent with the results of our work in which there were somewhat greater concentrations of total N and much lower concentrations of P in the PM-L soils, resulting in higher N:P ratios (i.e., P limited), greater soil C biomass, greater rates of both C and N biomass production, and a more fungaldominant microbial community in the PM-L soils.…”
Section: Discussionmentioning
confidence: 99%
“…Although N limitation is often cited as the main factor limiting ecosystem productivity, several studies have suggested that in many terrestrial ecosystems, P is central to the regulation of N budgets and may ultimately be more responsible than N for controlling plant biomass production (Cole & Heil, 1981;Eisele et al, 1989;Smith, 1992;Crews, 1993). Any ecological advantage given to N2-fixing organisms may not be evident if the limit set by 16 another nutrient, such as P availability, is also low (Crittenden et al, 1994).…”
Section: Influence Of Mineral and Nutrient Availability On N2-fixationmentioning
confidence: 99%
“…Several studies have found evidence to suggest that N2-fixing organisms increase in both abundance and fixation rate when P supply is high, especially in ecosystems with a relatively low supply of N (Eisele et al, 1989;Chapin et al, 1991;Vitousek & Howarth, 1991;Smith 1992, Crews, 1993, Kurina & Vitousek, 1999Davidson et al, 2002;Vitousek et al, 2002;Weiss et al 2005;. Due to the high P requirements of N2-fixing organisms, free-living N2-fixation rates in soil have been shown to correlate with availability of P in some ecosystems (Eisele et al, 1989;Chapin et al, 1991;Smith, 1992;Reed et al, 2007).…”
Section: Influence Of Mineral and Nutrient Availability On N2-fixationmentioning
confidence: 99%
See 2 more Smart Citations